Jacob burckhardt and the end of classicism (2003)
The purpose of this essay is to s ketch out some significant elements of the classical ideal, a model that had dominated both aesthetics since it rise as a philosophical discipline and historiography of art through Joachim Winckelman' wellknown studies. Starting from this considerations, it can be shown how Jacob Burckhardt 's reflections about history, in breaking with certain conception of history and with certain kind of historiography, take distance from the distinctive features of classicism.